A Global Systematic Review of Hepatitis C Elimination Efforts through Micro-Elimination - Lazarus, Jeffrey V.; Picchio, Camila A.; Byrne, Christopher J.; Crespo, Javier; Colombo, Massimo; Cooke, Graham S.; Dore, Gregory J.; Grebely, Jason; Ward, John W.; Dillon, John F. (Seminars in Liver Disease, 2022)
Microelimination targets specific subpopulations and/or geographic settings for hepatitis C virus (HCV) elimination. This review reports on global HCV microelimination literature published from 2013 to 2020. Data were extracted from publications to report a score based on the four key components defining microelimination. Sustained virologic response (SVR) and treatment initiation proportions were calculated for each manuscript and grouped means of these estimates were compared depending on microelimination score and care setting. A total of 83% of the studies were from high-income settings and mainly included people who use drugs or those incarcerated. Among manuscripts, 18 had “low” microelimination scores, 11 had “high” scores, and the differences in mean proportion who initiated treatment and achieved SVR between low and high score groups were statistically significant. Microelimination can be a useful complementary strategy for driving engagement in HCV treatment and cure. Our analysis suggests that adhering to more of the core microelimination components can improve outcomes. This study is registered with Prospero, registration identification: CRD42020175211.
Keywords: hepatitis C; microelimination; systematic review